The Degree of Teachers' Willingness to Use Technology in Education Based on the Competence of Knowledge of Technological Educational Content from their Perspectives - عبدالله بن خليفة العديل (مجلة العلوم التربوية والنفسية, 2024)
The study adopted technological pedagogical and content knowledge (TPACK) framework to assess the degree of teachers’ willingness to use technology in education It is important to know the impact of technology on education, especially when using technology and improving a teacher’s TPACK. This study used a survey and a comprehensive sampling technique that included 267 male and female teachers from different schools in the Kingdom of Saudi Arabia, who were randomly selected. The researcher collected the responses and provided descriptive statistics, including the mean, standard deviations, and rank. The results of the study indicated the extent of teachers’ willingness to use technology in education based on the competency of technological pedagogical and content knowledge, which reached a high degree. There were no statistically significant differences at the level of (0.05) in the responses of the study samples to the extent of teachers’ willingness to use technology in education according to the variables of gender, specialization, stage, experience, age, and training. Keywords: Willingness; Competence; Content knowledge; Pedagogical knowledge; Technological knowledge; TPACK.